2018
DOI: 10.1016/j.stem.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Myoepithelial Cells of Submucosal Glands Can Function as Reserve Stem Cells to Regenerate Airways after Injury

Abstract: Cells demonstrate plasticity following injury, but the extent of this phenomenon and the cellular mechanisms involved remain underexplored. Using single-cell RNA sequencing (scRNA-seq) and lineage tracing, we uncover that myoepithelial cells (MECs) of the submucosal glands (SMGs) proliferate and migrate to repopulate the airway surface epithelium (SE) in multiple injury models. Specifically, SMG-derived cells display multipotency and contribute to basal and luminal cell types of the SMGs and SE. Ex vivo expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 66 publications
5
107
0
1
Order By: Relevance
“…It was well established that the innervated MECs encircle the submucosal glands and mediate mucus secretion in response to neural inputs, which can activate massive secretory responses after stimulation by irritants and toxins (also reviewed in Boers et al 86 and Yei et al 120 ). 37,42,121 However, recent work by Lynch et al 122 and Tata et al 123 have explained the potency of MECs in generating seven cell types of surface airway epithelium and the submucosal gland following airway injury. These can be activated via Sox9 or Lef-1 transcriptional signaling, and they can be exploited for regenerative medicine.…”
Section: Alveolar Cells and Associated Diseasesmentioning
confidence: 99%
“…It was well established that the innervated MECs encircle the submucosal glands and mediate mucus secretion in response to neural inputs, which can activate massive secretory responses after stimulation by irritants and toxins (also reviewed in Boers et al 86 and Yei et al 120 ). 37,42,121 However, recent work by Lynch et al 122 and Tata et al 123 have explained the potency of MECs in generating seven cell types of surface airway epithelium and the submucosal gland following airway injury. These can be activated via Sox9 or Lef-1 transcriptional signaling, and they can be exploited for regenerative medicine.…”
Section: Alveolar Cells and Associated Diseasesmentioning
confidence: 99%
“…In the epithelium, FOXJ1 + human ciliated cells exhibit a precursor state marked by FOXN4 and MCIDAS , as well as a mature state marked by SNTN and CDHR3 , consistent with our discoveries in mice ( Figures 7A and S7A-B). Within basal cells marked by TP63 , SOSTDC1 , and KRT14 , a subpopulation distinctive from the others expresses SOX9 (Basal_SMG in Figure 7A), suggesting its origin from the submucosal gland (SMG) (Tata et al, 2018), a major structural difference between human and mouse trachea. The SOX9 negative basal population hence likely corresponds to apical basal cells which are located in the surface epithelium (SE) (Basal_SE in Figure 7B).…”
Section: Mouse and Human Airways Share Similar Cellular Landscape Durmentioning
confidence: 99%
“…Using multiple lineage tracing techniques along with single-cell transcriptome analysis, two recent reports have shown that MECs express Acta2 and an Acta2-creERT2 mouse line can be used to trace their fate after injury. Upon severe but not mild injury nor during homeostatic turnover, these studies indicate that a portion of Acta2 + MECs can proliferate, migrate out of the SMG, acquire a basal cell-like phenotype, and repopulate secretory and multiciliated cells of the trachea in mice (Lynch et al 2018;Tata et al 2018). The investigators have called MECs "reserve" stem cells, since they appear to be activated only after severe injury.…”
mentioning
confidence: 93%